The Representation of Youth in Pocari Sweat Television Advertisements - Hasah Hasanah (Passage, 2013)
This study entitled The Representation of Youth in Pocari Sweat Television Advertisements. This study aims to reveal the representation of youth in Pocari Sweat television advertisements and the ideologies behind that representation. This study used a qualitative descriptive method. The theory used in this study is the orders of signification proposed by Barthes (1957). The findings of this study show that youth is represented through the use of the visual elements of television advertisement (actors or actresses, settings, properties, frame sizes, camera angle, color saturation, and video editing) which show the positive characteristics of youth. In terms of ideologies, this study found three ideologies behind the representation of youth in Pocari Sweat television advertisements: feminism, nationalism, and commercialism.Feminism is viewed from the use of more actresses than actors; nationalism is reflected from the use of actors and actresses who have Japanese oriental faces; and commercialism is seen from the use of actors and actresses who have white or bright skin, and the representation of youth who has good characteristics in this life. From those three ideologies, commercialism is the dominant ideology found in that representation.Keywords: Representation, Youth, Advertisements, and Ideologies